Optimalisasi Pengelolaan Limbah Organik Rumah Tangga Melalui Produksi Eco-Enzyme untuk Mendukung Ekonomi Hijau di Desa Bulucindea - Rahmi, Rahmi; Syarif, Asriyanti; Ibrahim, Juliani; Indah Yani, Fitri; Rahayu Anwar, Andi; Insana Salam, Nur; Wahyu, Farhanah; Mansida, Amrullah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community engagement program was conducted to address household organic waste issues in Bulu Cindea Village by introducing eco-enzyme production as a practical and environmentally friendly solution. The activity aimed to improve community awareness, strengthen household-level waste management practices, and create economic opportunities through the utilization of organic kitchen waste. The implementation method consisted of community education sessions, hands-on training, and guided mentoring. A total of 25 participants, all members of the local women’s group, were involved in the activity. They were first introduced to the environmental impacts of unmanaged organic waste, followed by direct practice in preparing mixed organic materials, measuring ingredients, and setting up fermentation containers under supervised instruction. The mentoring process supported participants during the initial fermentation phase and introduced potential household uses and income-generating opportunities from eco-enzyme products. The activity resulted in significant improvements in knowledge and skills, as demonstrated by pre- and post-activity assessments, and all participants successfully produced at least one fermentation unit to be continued at home. Participants also reported reduced household waste volume and a better understanding of how eco-enzyme production can support daily needs, such as plant care and cleaning, while offering potential for micro-business development. This activity highlights the community’s capacity to adopt simple environmentally friendly technologies and demonstrates that empowering women as key actors can strengthen sustainable household waste management. The findings show that eco-enzyme activities can serve as an entry point for promoting green economic practices in rural coastal communitie